PENERAPAN LKS BERORIENTASI LIFE SKILL TERHADAP HASIL BELAJAR SISWA KELAS XI SMA PADA MATERI SISTEM PEREDARAN DARAH - MUHIMMATUL KARIMAH, NURUL (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
A research application of life skills-oriented worksheets on circulatory system materials has been conducted. The study aims to describe the increase of cognitive learning outcomes of students. This study used a pre-experimental design of pre-test and post-test group. The population of this study is all students of class XI IPA SMA. The sample in this research is the students of class XI IPA 1, SMAN 1 Ngoro Jombang. The results show that there is an increase of student learning outcomes from pre-test to post-test that are indicated by the results of classical mastery of 11.1% to 82.3%. These show that the application of life skills oriented worksheet on circulatory system matter can be done well and was be able to increase student learning outcomes. Keywords: Life skills, application of the worksheets, circulatory system